Analysis of The Relationship Between Learning Interest and Learning Outcomes in Problem-Based Learning with Video Media - Anisa Nuraini, Sulis Janu Hartati, Sunardjo (Journal of Educational Studies, 2025)
This research seeks to: (1) investigate the connection between students' motivation to learn and their academic performance, (2) explore variations in the degree of learning motivation, and (3) assess differences in academic outcomes between students who receive counseling through a video-assisted Problem-Based Learning (PBL) approach and those who do not at SMKN 1 Robatal. This research makes use of a Non-Equivalent Control Group strategy inside a quasi-experimental design. A control group received no treatment and the experimental group received PBL with video assistance; participants were randomly allocated to one of the two groups. A questionnaire to gauge motivation for learning and an accomplishment exam were among the instruments used. When analysing the data, the Mann-Whitney U test was used to compare the groups and Spearman's correlation was used to look for correlations. The results show that: (1) learning motivation and academic achievement are not significantly correlated (r = -0.161; p > 0.05); (2) the experimental and control groups differ significantly in levels of motivation (Asymp. Sig. = 0.000 < 0.05); and (3) the two groups achieve significantly different academic outcomes (Asymp. Sig. = 0.000 < 0.05). Although no statistically significant relationship was found between the variables, the research found that students' willingness to learn and academic achievement were both improved separately with the use of the PBL paradigm through video-supported counselling.